The indirect carbon emission from household consumption in China between 1995–2009 and 2010–2030: A decomposition and prediction analysis. (February 2019) - Xia, Yan; Wang, Huijuan; Liu, Weidong
Highlights: A framework of determining and predicting to assess indirect emissions is developed. Indirect carbon emissions from household consumption is redefined. Multivariable regressions is inserted into IO and SDA model to predict indirect emissions. The population variable has a positive role. Abstract: Indirect carbon emissions from households can be redefined and recalculated using an input-output model. This paper combines multivariate regression analysis with input-output technology and a structural decomposition analysis to examine their impact and predict carbon emissions in the future. The results show that urban employment, rapid urbanization, and the two-child policy are the main reasons for the population variable having a magnifying effect on increasing indirect carbon emissions. Growing household incomes and improved living standards will pose a serious threat to responses to climate change in most developing countries. The growth rate of indirect carbon emissions from household consumption will slow under the two-child policy, after adjusting for other determinants such as consumption composition and technical progress in energy-intensive sectors. The steady and continuous increase of indirect emissions is mainly trouble lies the stable consumption of secondary industry products and the rapid growth in consumption of tertiary industry products. This paper also presents several policy implications for the government and other decision-making organizations.